2015
DOI: 10.5152/ejp.2015.76476
|View full text |Cite
|
Sign up to set email alerts
|

Does the Finding of Small Airway Obstruction in Pulmonary Function Tests Effect End-Expiratory Carbonmonoxide Level?

Abstract: Objective: End-expiratory CO level, which is used to test smoking cessation is known to be effected by many factors. We aimed to evaluate effect of small airway obstruction (SAO) on end-expiratory CO levels. Methods:The study population consisted of cases who applied to smoking cessation clinic between April-December 2014. The duration of smoking (pack-years), pulmonary function tests (PFT) and end-expiratory carbonmonoxide (CO) were noted at first visit. The cases were questioned for last time of smoking and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…23 Similar results to researchers obtained by Salepci et al, expiratory CO levels were also not found to have a significant correlation with force expiratory flow/ FEF 25-75% ((r =-0.05, p=0.527). 18 This lack of correlation could be caused by several factors including no data on how many cigarettes were smoked in the last 12 hours and how long the respondent had not smoked before the examination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Similar results to researchers obtained by Salepci et al, expiratory CO levels were also not found to have a significant correlation with force expiratory flow/ FEF 25-75% ((r =-0.05, p=0.527). 18 This lack of correlation could be caused by several factors including no data on how many cigarettes were smoked in the last 12 hours and how long the respondent had not smoked before the examination.…”
Section: Discussionmentioning
confidence: 99%
“…12 This study aims to assess the relationship between the degree of smoking and exhaled carbon monoxide levels with lung function in online motorcycle taxi drivers. 18…”
Section: Introductionmentioning
confidence: 99%